The Effect of Word of Mouth (WOM) and Marketing Strategy in Mediating Consumer Loyalty to UMKM Product Purchasing Decisions - Agustin, Resty; Soetjipto, Budi Eko; Wardana, Ludi Wishnu (PT Maju Malaqbi Makkarana, 2025)
This research systematically explores the roles of Word of Mouth (WOM) and marketing strategies in mediating consumer loyalty and its impact on purchasing decisions for Micro, Small, and Medium Enterprises (MSMEs) products. Applying a Systematic Literature Review (SLR) method, this study synthesizes scholarly articles sourced from major academic databases such as Scopus, ScienceDirect, Google Scholar, and ProQuest, covering publications from the past decade. The selection of literature followed rigorous procedures including identification, screening, and eligibility assessments, with strict inclusion criteria to ensure the relevance and quality of the reviewed studies. The analysis reveals that WOM significantly influences consumer perception and trust, while well-implemented marketing strategies help establish long-term consumer engagement. These two factors contribute positively to consumer loyalty, which in turn plays a pivotal role in shaping purchasing behavior toward MSME products. Additionally, consumer loyalty is identified as a key mediating variable that reinforces the relationship between WOM, marketing strategies, and purchase decisions. The findings offer valuable insights for both academic and practical perspectives, particularly in designing relationship-oriented marketing approaches to strengthen MSME competitiveness.